Effect of aminoacids on the fungicidal activity of quaternary ammonium salts - Jerzy Piątkowski (Acta Mycologica, 2013)
Amphipatic compounds exhibit an antimicrobial action both on bacteria and fungi. It is caused by a penetrative property of hydrophobic carbon chain of the compuound into a plasma membrane as well as by additional interaction of membrane elements and a hydrophilic amphipathic compound head. Bactericidal and fungicidal activity of this compound strongly depends on chemical environmental factors. In general, microorganisms are not as sensitive in a full medium as in a minimal one and the level of sensitivity rises when the amphipatic compounds are presend in destilled water. Similarly, the sensitivity is stronger in fluid than on solid medium. Our researches revealed however that some aminoacids, although they are complex organic compounds, increase the microbial sensitivity to some tested compound. This efect depends on a microorganism and on a kind of compound. The highest hipersensitivity has been observed against yeast-like fungi when arginine was a cooperating aminoacid. The effect concerns Trichosporon but not E.coli, not occurs in relation to SDS, quaternary ammonium salt IA, and bisammonium salts. Certainly the effect exhibit QAS, which have simple composition of hydrophilic „head” consisting only of methyl group, attaching to alkilic chain possessing keton group, build of 14 or 16 carbon atoms.